Diode-pumped passively Q-switched Nd:YVO4 laser using a reticularly ordered single-walled carbon nanotube saturable absorber. (1st December 2017) - Zhang, Xiaodong; Zhao, Shengzhi; Li, Ying; Zhang, Yan; Li, Dechun; Yang, Kejian; Li, Xiangyang; Wang, Reng
Highlights: Reticular ordered SWCNT solution is achieved by self-assembly method. Reticular ordered SWCNT was used as saturable absorber in passively Q-switched laser. Reticular ordered SWCNT based SA have better energy storage ability. Abstract: In this letter, we demonstrate a diode-pumped passively Q-switched Nd:YVO4 laser with reticularly ordered single-walled carbon nanotube as saturable absorber. Stable Q-switched pulses with a pulse energy of 0.322 μJ, a pulse width of 78.7 ns and a pulse repetition rate of 410.3 kHz have been obtained. Compared with the passively Q-switched laser with carbon nanotubes dispersed by sodium dodecyl sulfate (SDS), the laser with reticularly ordered single-walled carbon nanotube can produce shorter pulses and higher peak power at almost the same incident pump power. The results suggest that the reticularly ordered single-walled carbon nanotube can be an attractive candidate of saturable absorber for Q-switched laser.